Ecological and functional biodiversity in a marine algal-virus system: genotypes, phenotypes and their ecological significance - Nissimov, Jozef I. (2013)
Coccolithoviruses are large dsDNA viruses infecting the cosmopolitan calcifying marine phytoplankton Emiliania huxleyi. Therefore they are instrumental components of algal bloom demise and thus agents contributing significantly to biogeochemical cycling in the oceans. Several coccolithovirus strains exist in culture and have been used so far to study the co-evolutionary arms-race between them and their unicellular host in naturally occurring or induced blooms in the North Atlantic Ocean and the fjords of Norway. However, little is known of their distribution in non-bloom conditions, their natural diversity in times of reduced infectivity rates, and the role of functionally important genes found in natural coccolithovirus communities. Even less is known about their genetic differences and the phenotypic consequences of these differences on their infection dynamics. Hence here a three dimensional approach was undertaken, during which the genomes of several coccolithovirus strains were analysed, their diversity in the global ocean characterised, and their phenotypic properties as seen from their infection dynamics with their host established. It was revealed that although coccolithoviruses share a common subset of core genes, they differ in a large proportion of their genomic material, as seen from the presence and/or absence of large sub-clusters of functionally unknown genes. Moreover, a gene that encodes for a phosphate scavenging mechanism (phosphate permease) was truncated from the genome of the Norwegian isolate EhV-99B1 but not from any other strain, while a gene encoding for the virulence factor sialidase was truncated only in the genomes of the English Channel strains isolated in 2001. The discovery of an additional gene that is potentially involved in the regulation of sphingosine and ceramide intermediates during the de novo virus encoded sphingolipid biosynthesis pathway was also intriguing, and the extent of gene homology to host genes (i.e. almost 13% of the analyzed genomes) highlighted the importance of horizontal gene transfer events in the co-evolution between algal hosts and their viruses. Secondly, it was established that virus competition over its resource, the host-cell, is fierce and that during host coinfection, some viruses (i.e. EhV-207) were superior to others (i.e. EhV-86) in their quicker utilisation of the host metabolic machinery and possibly shorter latency period within the infected cells. The biogeochemical and evolutionary implications of these distinct phenotypic properties are far reaching as in the environment there would be hundreds of different virus strains fighting over a few dominant hosts, with “losers” and “winners” coming and going from a particular niche, affecting the recirculation of nutrients and carbon at different rates. Finally, by community fingerprinting cococlithoviruses in the global ocean with phylogenetic markers (major capsid protein) and functional markers (serine palmitoyltransferase) it was discovered that the diversity of these viruses increase with depth, and that the 3D structure of the SPT protein (involved in the propagation of host cell death) differs among strains, dictated by a variant amino acid linker region between the two domains of the protein, LCB1 and LCB2, potentially influencing the efficiency of the virus encoded sphingolipid biosynthesis pathway. This study is an important first step in understanding the role of coccolithoviruses, their evolution, their functional characteristics, and the possible implications of the latter to biogeochemical cycling and global climate and primary production predictions.